2019
DOI: 10.1186/s12904-019-0448-z
|View full text |Cite
|
Sign up to set email alerts
|

Talking about end of life in general palliative care – what’s going on? A qualitative study on end-of-life conversations in an acute care hospital in Denmark

Abstract: Background End-of-life (EOL) conversations in hospital should serve to give patients the opportunity to consider future treatment options and help them clarify their values and wishes before it becomes relevant to make decisions about treatment. However, it is known that EOL conversations are not performed systematically in hospital. This may mean that patients and their relatives do not address EOL issues. There is a lack of knowledge about who is responsible for conducting these conversations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 46 publications
(46 reference statements)
5
47
0
3
Order By: Relevance
“…The modules provided a framework by which health professionals could proactively respond to patient and carer needs. Participant responses in our study are consistent with other research that identifies a need for communication skills training, how to best care for family carers and improvement in multidisciplinary team communication about patient and carer needs [ 33 , 37 ]. Since its launch, more than 20,000 health professionals have registered with EOLE with over 36,000 module completions, indicating an interest in this general level of education about end-of-life care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The modules provided a framework by which health professionals could proactively respond to patient and carer needs. Participant responses in our study are consistent with other research that identifies a need for communication skills training, how to best care for family carers and improvement in multidisciplinary team communication about patient and carer needs [ 33 , 37 ]. Since its launch, more than 20,000 health professionals have registered with EOLE with over 36,000 module completions, indicating an interest in this general level of education about end-of-life care.…”
Section: Discussionsupporting
confidence: 86%
“…Enhancing health professionals’ ability to initiate these conversations is vital as patients don’t always speak up about approaching end of life, assuming the health professional will initiate this [ 35 , 36 ] Engaging in end-of-life care with patients has been identified as one of the most challenging but most important considerations for health professionals when caring for people at the end of life. [ 37 39 ]. Although communication skills training is included in most health professional education, minimal time is spent on how to broach end-of-life conversations [ 7 , 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it showed that some physicians consider hastening the end of life, even without explicit patient requests, as an act of mercy [29]. Our study found very little conversation takes place between physicians, patients and family members on the dying process and end-of-life decisions, a nding in line with previous studies from countries like the United States and Denmark [30]. It is possible these ndings represent a rmly-engrained paternalistic culture which persists among Colombian health professionals.…”
Section: Discussionsupporting
confidence: 89%
“…7,15 Doctors are often expected to initiate SICs and nurses to provide emotional comfort, address concerns, and act as support persons. 7,10,14 All these barriers speak to the need for a coordinated interprofessional team approach to SICs. 15 The present study aims to address some of these barriers by promoting a coordinated interprofessional team approach to SICs through a quick and efficient collaborative method for identifying patients for SICs.…”
Section: Introductionmentioning
confidence: 99%